2019
DOI: 10.1101/560284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of new inhibitors of the toxoplasma gondii by using in-silico drug repurposing

Abstract: Introduction:The common treatment for toxoplasmosis was pyrimethamine. In recent years, it has been found that this parasite is getting resistant to this treatment, therefore urgent alternative treatments are needed. Material and Methods: In this study, by using drug repurposing and in silico methods we tried to make a selective treatment by inhibiting the Calcium-Dependent Protein Kinase 1 from Toxoplasma gondii which doesn't exist in mammalians. We screened the FDA approved drugs by molecular docking and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Therefore, it could be a potential candidate for inhibiting Toxoplasma gondii viability. In a similar study ( 10 ), using a molecular docking method on FDA approved drugs, which included Cefpiramide, Cefotiam and Ponatinib, attempted to develop a selective treatment by inhibiting Protein Kinase 1 from T. gondii. The authors found that all compounds could bind strongly to the active site of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it could be a potential candidate for inhibiting Toxoplasma gondii viability. In a similar study ( 10 ), using a molecular docking method on FDA approved drugs, which included Cefpiramide, Cefotiam and Ponatinib, attempted to develop a selective treatment by inhibiting Protein Kinase 1 from T. gondii. The authors found that all compounds could bind strongly to the active site of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, available treatments for toxoplasmosis, such as the combination of pyrimethamine with sulfadiazine, have some limitations and side effects that include nausea, headache, folic acid deficiency, aplastic anemia, skin rash and hematologic toxicity ( 8 10 ). Investigations into the utility of medicinal plants as potential treatments for toxoplasmosis are currently underway.…”
Section: Introductionmentioning
confidence: 99%